MANAJEMEN PRODUKSI KONTEN DI SOSIAL MEDIA HUMAS POLRESTABES PALEMBANG - Syahban, M Rifki; Misnawa, Desy (Kohesi: Jurnal Sains dan Teknologi, 2025)
In today's digital era, social media has become a highly effective communication tool for reaching a wide audience. As a national security institution, the Palembang Metropolitan Police (Polrestabes Palembang) also utilizes social media as a platform for public communication, direct interaction, and transparency to enhance public trust. Through an Independent Study program conducted within the Public Relations Division of Polrestabes Palembang, the author was directly involved in managing and producing social media content. This process included idea brainstorming, on-site coverage, and editing to produce content that is both relevant and aligned with the image of the police institution. Various types of content were created, including flyers, social activity documentation videos, educational memes, and informative podcasts. In addition, the author observed the internal workflow and communication structure within the Public Relations Division to provide constructive evaluation and suggestions. The results of this activity demonstrate that social media publication plays a significant role within the police institution. Therefore, the role of social media as a publication tool should continue to be strategically and creatively optimized to support performance and strengthen public trust in Polrestabes Palembang.